2021
DOI: 10.1093/sleep/zsab242
|View full text |Cite
|
Sign up to set email alerts
|

Sleepless in COVID-19: racial disparities during the pandemic as a consequence of structural inequity

Abstract: Study Objectives Insomnia has been on the rise during the 2019 coronavirus disease (COVID-19) pandemic, which may disproportionately affect racial minorities. This study characterized racial disparities in insomnia during the pandemic and evaluated mechanisms for such disparities. Methods Participants included 196 adults (48 Black) from a 2016–2017 clinical trial of insomnia treatment who were reevaluated in April 2020. Race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
(67 reference statements)
0
12
0
1
Order By: Relevance
“…The type of population was categorized as follow: adolescents (6 studies) [ 71 , 81 , 87 , 92 , 108 , 138 ], children (1 study) [38], general population (66 studies) [ 40 , 42 , 43 , 46 , 48 , 49 ], [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , 59 , 60 , [64] , [65] , [66] ], [ [68] , [69] , [70] , 72 , 73 , 76 , [78] , [79] , [80] ], [ [82] , [83] , [84] , [85] , 88 , 89 , 101 , 103 ], [ 104 , 109 , 110 , 113 , 117 , 120 , 121 ], [ 123 , 128 , 129 , 131 , 134 , 135 , 137 ], [ 139 , [141] , [142] , [143] , [144] , [145] , 147 , [150] , [151] , [152] ], [ 154 <...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of population was categorized as follow: adolescents (6 studies) [ 71 , 81 , 87 , 92 , 108 , 138 ], children (1 study) [38], general population (66 studies) [ 40 , 42 , 43 , 46 , 48 , 49 ], [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , 59 , 60 , [64] , [65] , [66] ], [ [68] , [69] , [70] , 72 , 73 , 76 , [78] , [79] , [80] ], [ [82] , [83] , [84] , [85] , 88 , 89 , 101 , 103 ], [ 104 , 109 , 110 , 113 , 117 , 120 , 121 ], [ 123 , 128 , 129 , 131 , 134 , 135 , 137 ], [ 139 , [141] , [142] , [143] , [144] , [145] , 147 , [150] , [151] , [152] ], [ 154 <...…”
Section: Resultsmentioning
confidence: 99%
“…The total scores ranged from 3 to 6. Most of the studies (114) [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], [ [63] , [64] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , [75] , [76] , [77] ], [ [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , 91 , [93] , [94] , [95] , [96] , [97] , [98] , [99] ], [ [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [113] , …”
Section: Resultsunclassified
“…First, the majority of respondents were White participants and women, which is important as some studies have found that insomnia was elevated among women during the pandemic (Kang et al, 2020 ; Li et al, 2020 ). COVID‐19 and COVID‐19‐related insomnia have disproportionately impacted Black Americans (Cheng et al, 2022 ) and it will be important to study the effect of worry on insomnia among Black participants during the COVID‐19 pandemic. Second, as is to be expected by a study that did not pay participants for survey completion, only about one‐third of participants completed all three study assessments.…”
Section: Discussionmentioning
confidence: 99%
“…These findings coincide with previous research suggesting that the influence of COVID-19 specific stressors did not uniquely influence sleep quality by gender, race/ethnicity, or educational attainment [ 19 ]. The findings are troubling as during one of the most dramatic and abrupt increases in the reported sleep duration on record, sleep disparities across gender, race/ethnicity, and educational attainment remained [ 22 , 38 ]. That is, Americans seemingly consistently changed their sleep duration in the early stages of the pandemic resulting in stable levels of inequality in sleep as before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Black adults and Hispanic adults report significantly shorter sleep durations than non-Hispanic White adults [ 20 ]. In 2020, the pandemic disproportionately influenced non-Hispanic Black Americans and Hispanic Americans([ 21 ], including their insomnia [ 22 ]. Black Americans and Hispanic Americans who were more likely to work “frontline”, on-site jobs, and in service sectors that were economically decimated in the tens of millions [ 23 ].…”
Section: Introductionmentioning
confidence: 99%